COLLEGE STUDENTS’ PHYSICAL AND MENTAL HEALTH EXERCISE BASED ON TENNIS - Li,Yan (2021)
ABSTRACT College students are often under great pressure, and their physical and mental health is the focus of attention in college education. In order to cultivate high-quality talents and relieve the pressure of college students, many colleges and universities have set up a variety of sports courses, including tennis courses. Analyzing the influence of tennis on the physical and mental health of college students, this study studies the situation of college students participating in tennis by consulting literature, designing questionnaires and using an experimental measurement method, while it constructs the physical health evaluation index and mental health evaluation index of college students. On this basis, this study evaluates the influence of tennis on students’ physical and mental health. The results show that tennis has a positive impact on the physical and mental health of college students. Tennis can not only enhance college students’ cardiopulmonary function and muscle strength, but also cultivate students’ independent personality, eliminate depression tendency, make students independent, flexible and active, which is conducive to the development of students’ mental health. It is hoped that this study can provide some reference for the research of college students’ physical and mental health exercise based on tennis.